Chitosan-reduced graphene oxide composites with 3D structures as effective reverse dispersed solid phase extraction adsorbents for pesticides analysis. Issue 17 (25th July 2019) - Zhang, Minglu; Ma, Guicen; Zhang, Lin; Chen, Hongping; Zhu, Li; Wang, Chen; Liu, Xin
Abstract : Chitosan-reduced graphene oxide composites with 3D structures (3D CS-rGO) were prepared via a facile solvothermal synthetic strategy. It exhibited high adsorption capacities towards different types of tea matrix interferences. Abstract : Chitosan-reduced graphene oxide composites with 3D structures (3D CS-rGO) were prepared via a facile solvothermal synthetic strategy. The reduction of GO and crosslinking of rGO nanosheets with CS into 3D structures were achieved simultaneously in one step. The resulting 3D CS-rGO composite achieves high adsorption capacities of catechins, caffeine and pigments from tea acetonitrile extraction, especially for catechins, which is 10 times higher than that of GO (179.3 mg g −1 vs. 18.7 mg g −1 ). The 3D CS-rGO composite exhibits the best removal efficiency of matrix interference in comparison to other traditional adsorbents, which could diminish the matrix effect on targeted pesticides by 1%–55%. A determination method of 70 kinds of pesticides is successfully established for tea based on 3D CS-rGO composite as an efficient reverse dispersed solid phase extraction adsorbent. The established method has the great advantages of operation simplicity, being time saving and high purification performance using only one kind and a low amount of adsorbent. 3D graphene based materials are expected to be promising adsorbents for sample pretreatment in trace contaminant analysis of complex food samples.